Synthesis and chiroptical properties of cylindrical macrocycles comprising two calix[3]aramide moieties. Issue 2 (4th November 2019) - Saito, Yuuki; Satake, Misa; Mori, Ryuichi; Okayasu, Misaki; Masu, Hyuma; Tominaga, Masahide; Katagiri, Kosuke; Yamaguchi, Kentaro; Kikkawa, Shoko; Hikawa, Hidemasa; Azumaya, Isao
Abstract : Novel chiral macrocyclic aromatic amides of medium molecular weight were synthesized by the one-step amide coupling of a bis(alkylamino)terphenyl diacid as monomer. Abstract : Calix[3]aramide-based cylindrical macrocycles were synthesized by the one-step amide coupling reaction of a monomer containing two meta -alkylaminobenzoic acid units linked by para -phenylene bridges. The major products included a meso-form and an enantiomeric pair, with stereochemistry derived from the direction of the amide bonds and their fixed conformation. Mirror-image ECD, VCD, and CPL spectra were observed in the enantiomeric pair and the absolute structure was determined by comparing measured and calculated ECD and VCD spectra.